Unprecedented non-hysteretic superelasticity of [001]-oriented NiCoFeGa single crystals - Chen, Haiyang; Wang, Yan-Dong; Nie, Zhihua; Li, Runguang; Cong, Daoyong; Liu, Wenjun; Ye, Feng; Liu, Yuzi; Cao, Peiyu; Tian, Fuyang; Shen, Xi; Yu, Richeng; et al. (Nature materials, 2020)
Superelasticity associated with the martensitic transformation has found a broad range of engineering applications 1 , 2 . However, the intrinsic hysteresis 3 and temperature sensitivity 4 of the first-order phase transformation significantly hinder the usage of smart metallic components in many critical areas. Here, we report a large superelasticity up to 15.2% strain in [001]-oriented NiCoFeGa single crystals, exhibiting non-hysteretic mechanical responses, a small temperature dependence and high-energy-storage capability and cyclic stability over a wide temperature and composition range. In situ synchrotron X-ray diffraction measurements show that the superelasticity is correlated with a stress-induced continuous variation of lattice parameter accompanied by structural fluctuation. Neutron diffraction and electron microscopy observations reveal an unprecedented microstructure consisting of atomic-level entanglement of ordered and disordered crystal structures, which can be manipulated to tune the superelasticity. The discovery of the large elasticity related to the entangled structure paves the way for exploiting elastic strain engineering and development of related functional materials. NiCoFeGa single crystals exhibit large non-hysteretic superelasticity over broad temperature and composition ranges. It is attributed to the continuous phase transition with applied stress, which is related to the fluctuation of entangled ordered and disordered crystal structures.